Mastery of Religious and Heroic Values in the Drama Script Pattimura by Farid Latif in Drama Learning for VIII Grade Students at State Junior High School 7 Ambon - Angwarmase, Kristina; Lewier, Mariana; Rumalean, Iwan (Mirlam: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Drama learning is one of the materials presented in literature learning at the junior high school level. However, in reality, there are still several obstacles that need to be considered by educators and for which solutions need to be found. The problem observed in this study relates to the mastery of life values in drama scripts and is found in SMP Negeri 7 Ambon, 7th grade. This study is quantitative descriptive, focusing on the mastery of religious and heroic values in the drama script "Pattimura" by Farid Latif. The purpose of this study is to explain the mastery of religious and heroic values in drama learning for 8th-grade students at SMP Negeri 7 Ambon. The research sample consisted of 30 students out of 276, selected thru a lottery sampling method. Data were analyzed using SPSS version 23. The research results showed that eighth-grade students at SMP Negeri 7 Ambon mastered religious and heroic values in the play "Pattimura" by Farid Latif. This is proven by the results of the objective test.